Photochemical performance of ZnO nanostructures in dye sensitized solar cells - Das, Partha Pratim; Mukhopadhyay, Soumita; Agarkar, Shruti A.; Jana, Arpita; Devi, P. Sujatha (Solid State Sciences, 2015)
In this work, the photoconversion efficiencies of ZnO having diverse microstructures and structural defects have been investigated. A conversion efficiency of 138% was achieved for the DSSCs fabricated with as prepared ZnO nanorods having minimum vacancy defects and a favourable one dimensional directional pathway for electron conduction. The DSSCs fabricated with ZnO nanoparticles exhibited relatively low conversion efficiency of 1.004% probably due to multiple trapping/detrapping phenomena within the grain boundaries and ZnO flowers though exhibited a high dye adsorption capability exhibited the lowest conversion efficiency of 0.59% due to a high concentration of structural defects. Based on the experimental evidences, we believe that the type of defects and their concentrations are more important than shape in controlling the overall performance of ZnO based DSSCs. (C) 2015 Elsevier Masson SAS. All rights reserved.
Keywords: DSSC; Efficiency; Emission; Structural defects; ZnO